Responsibility of health providers in domestic violence reporting - Saliba, Orlando; Garbin, Cléa Adas Saliba; Garbin, Artênio José Isper; Dossi, Ana Paula (Revista de Saúde Pública, 2007)
Domestic violence reporting by health providers contributes to the epidemiological assessment of the magnitude of the problem, which allows the development of specific programs and actions. The aim of the study was to assess the level of responsibility of these providers towards reporting violence, especially domestic violence, and potential related legal and ethical implications. The Brazilian legislation and ethics code of Medicine, Dentistry, Nursing and Psychology were studied. Legal sanctions are found in the Criminal Law of Misdemeanor Offenses, the Child and Adolescent Statute, the Elderly Statute and in the law establishing mandatory reporting of violence against women. There are also penalties in all ethics codes reviewed. It is concluded that health providers have the legal duty of reporting known domestic violence cases and they can even be charged with omission.